Ethnoscience Digitalization in Indonesian Science Learning: Systematic Literature Review of Current Trends, Media, and Impacts - Nida'ul Khasanah; Sigit Saptono; Novi Ratna Dewi; Dyah Rini Indriyanti (FKIP - Universitas Riau, 2026)
This study aims to analyze publication trends, media characteristics, the distribution of science topics, and the impacts of digital ethnoscience media on students' scientific skills in Indonesia. Employing a Systematic Literature Review (SLR) methodology on 30 articles published between 2017 and 2026, the study reveals that publication volume surged starting in 2024, peaking in 2025 with 16 articles. The research focus significantly shifted from theoretical cultural exploration in 2023 to the development of ready-to-use digital media in 2024–2025, dominated by interactive mobile/web applications (40%) and digital content (30%). However, the distribution of science topics remains uneven, predominantly clustering around environmental science and general science, leaving abstract concepts related to living organism physiology largely unaddressed. Furthermore, the developed digital tools prove highly effective in training students' practical skills, such as Science Process Skills (0.76) and Problem-Solving (0.77) through the aid of VR or interactive games, whereas students' scientific reasoning skills remain at the lower bound of the moderate category (0.40). Future research is recommended to develop interactive simulation media, such as virtual laboratories for abstract topics, and to implement more rigorous experimental methods in classroom settings.